True cancer stem cells exhibit relative degrees of dormancy and genomic stability - Sanford H. Barsky; Krista Mcphail; Justin Wang; Jordan Dillard; Crystal J. Beard; Yin Ye (Neoplasia: An International Journal for Oncology Research)
Background: Cancer stem cells in human tumors have been defined by stem cell markers, embryonal signaling pathways and characteristic biology, ie., namely the ability to repopulate the proliferating population. However, even if these properties can be demonstrated within a tumor cell subpopulation, it does not mean that they are truly hierarchical stem cells because they could have been derived from the proliferating population in a reversible manner. Methods: Using a human PDX, Mary-X, that overall expressed a strong cancer stem cell phenotype, the study conducted both GPP-labelled retroviral transfection and fluorescent microsphere uptake studies to distinguish proliferating from dormant cells and array CGH to identify regions of amplifications (gains) and deletions (losses) on the overall Mary-X population and then applied derived probes by FISH on individual cells to identify a genomically stable subpopulation. Results: Whereas 97-99 % of the cells expressed retroviral GFP and not fluorescent particles and showed numerous gene amplifications and deletions, approximately 1-3 % of the cells showed the opposite. The subpopulation with the retained fluorescent microspheres and exhibiting genomic stability was significantly smaller in size than their GFP-expressing and genomically unstable counterparts. Sorting Mary-X spheroids on the basis of either CD133 or ALDH positivity further enriched for this subpopulation. Conclusions: These studies indicate that a truly biological cancer stem cell subpopulation exists that exhibits both dormancy and genomic stability. This subpopulation could not have been derived from the proliferating and resulting genomically unstable population and therefore represents a truly hierarchical stem cell subpopulation capable of only unidirectional differentiation.